Development of E-Modules of Reaction Rate Problem-Based Learning Model to Improve Students’ Critical Thinking Skills and Wasaka Character - Rusmansyah, Rusmansyah; Kusasi, Muhammad; Sapnah, Sapnah; Bakti, Iriani; Astuti, Resti Tri (Department of Chemistr Education Faculty of Teacher Training and Education Universitas Su, 2024)
This study aims to improve critical thinking skills and Wasaka characteristics through the development of a problem-based learning-based reaction rate e-module and to assess the validity, practicality, and effectiveness of the e-module. This research uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). In the analysis stage, researchers assess the needs of teaching materials, characteristics of students, and learning objectives. The design stage includes material collection, outline preparation, and e-module prototype design. At the development stage, the author conducted e-module development and validation with expert validators. In the implementation stage, the learning application using the e-module was carried out in class XI B SMA Negeri 10 Banjarmasin with as many as 34 students, which involved practicality and effectiveness tests. At this stage, students learn via e-modules that are accessed via their respective cellphones. The evaluation stage is carried out with 2 types, namely, summative evaluation through pretest and posttest and formative evaluation, by evaluating each stage by revising the e-module. The results showed that the e-module was very valid (score of 4.85), very practical (score of 92.75), and effective in improving critical thinking skills (N-Gain of 0.78) and Wasaka characteristics (N-Gain of 0.72). The indicators used in the critical thinking ability variable are the FRISCO (focus, reason, inference, situation, clarity and overview). In addition, the Wasaka character indicators used are responsibility, hard work and resilience. The results of this analysis indicate that the e-module is very valid, very practical, and very effective in applying the reaction rate material to improve critical thinking skills and Wasaka characteristics.